Vortex search algorithm for designing hybrid active power filter - Chau Minh Thuyen; Truong Khac Tung; Nguyen Hoai Phong (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper proposes a new multi-objective optimization design method for Hybrid Active Power Filter based on the Vortex Search algorithm. The Vortex Search algorithm belongs to the Single-Solution Based algorithm class of Metaheuristics algorithm. This design method has the advantage of fast execution time, high convergence speed and prevent local trap problems. The achieved results are multi-objective, such as minimum total harmonic distortion of the supply current and source voltage and satisfy many constraints such as system stability, resonance conditions of branches and limits of the parameters. Compared with the traditional design method, simulation results have proved that: the proposed design method is given with better results in minimizing total harmonic distortion of the supply current and source voltage.